Analisis Soal Penilaian Akhir Semester (PAS) Tema 6 ditinjau dari High Order Thingking Skills (HOTS) Pada Kelas VI SD Negeri 1 Klewor Tahun Ajaran 2019/2020 - Purbosari, Dewi; Sulistiya Dewi, Endah Rita; Sulianto, Joko (STKIP Andi Matappa Pangkep, 2021)
This study aims to analyze the final assessment items theme 6 reviewed High Order Thinking Skills (HOTS) in grade VI SD N 1 Klewor 2019/2020 academic year. This research uses qualitative research with descriptive method. The documents analyzed were in the form the Final Semester Assessment (PAS) Theme 6 for the 2019/2020 academic year. Data collection techniques using documentation. The data this study were obtained from interviews, and documentation. The results the analysis show that there are 3 categories 45 items. Namely, Lower Order Thinking Skills (LOTS) there are 11 multiple choice questions with a percentage 37%, 1 short entry question with percentage 10%, Middle Order Thinking Skills (MOTS) there are 10 multiple choice questions with percentage 33%, 9 short questions with percentage of the percentage 90%, 2 essay questions with percentage 40%, and High Order Thinking Skills (HOTS) there are 9 multiple choice questions with percentage 30%, 3 essay questions with percentage 60%. The overall percentage the 45 end-of-semester assessment questions Theme 6 â€œTowards a Healthy Societyâ€ class VI SD Negeri 1 Klewor Lower Order Thinking Skills (LOTS) is 26%, Middle Order Thinking Skills (MOTS) is 47%, and High Order Thinking Skills (HOTS) by 27%.